Wicked tendencies in policy problems: rethinking the distinction between social and technical problems. Issue 3 (14th August 2017) - Newman, Joshua; Head, Brian W
Abstract: Complex or intractable policy problems, often called 'wicked' problems, have been a feature of public policy research since the early 1970s. Observers have generally assumed that these wicked problems constitute a distinct category of policy problems, based on the notion that some problems – those characterised as substantially technical or scientific in nature – lend themselves to traditional linear problem-solving methods, whereas other problems that are social in nature tend to be wicked. By examining three cases where scientific knowledge is central to the debate – climate change, genetically modified foods and hydraulic fracturing – we argue that all policy problems can exhibit wicked tendencies, regardless of the amount of scientific information available to decision-makers. Therefore, the reliance on increased information in resolving wicked problems is unlikely to be sufficient or effective.